Digital Trust Formation and Generation Z Adoption of Islamic Financial Products: The Mediating Role of Brand Trust - Ainun Nurul Uzamah; Nurhidayat Nurhidayat (LifeSciFi, 2026)
The development of digital technology has changed the communication strategies of the financial industry, including Islamic financial institutions, in reaching Generation Z through digital platforms and social media. However, the adoption rate of Islamic financial products among Generation Z is still relatively low, so it is necessary to understand the factors that shape consumer trust in the digital environment. This study aims to analyze the influence of digital advertising, influencer endorsements, and e-WOM on the intention to adopt Islamic financial products among Generation Z, with brand trust as a mediating variable. The study used a quantitative approach with a survey method. Data were analyzed using PLS-SEM. The results showed that e-WOM has a positive and significant influence on brand trust and adoption intention, while digital advertising only has a significant effect on brand trust. Influencer endorsements do not have a significant effect on brand trust and adoption intention. In addition, brand trust is proven to be an important mediator in the relationship between e-WOM and digital advertising on adoption intention. This study emphasizes the importance of trust-based digital communication strategies and authentic consumer experiences in increasing the adoption of Islamic financial products among Generation Z.